2021
DOI: 10.12669/pjms.38.1.4010
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bent leg raise technique and neurodynamics in patients with radiating low back pain

Abstract: Objective: To compare the effectiveness of bent leg raise technique and neurodynamics in patients with low back pain that radiates up to the knee. Methods: The pre-test post-test control group study was conducted at Department of Physical therapy, Maqsood Medical Complex and General Hospital Peshawar from February to July 2019. Patients with radiating low back pain of both genders aged 18-60 years were included in the study. Patients were divided into Group-A and Group-B. Group-A patients received Mullig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Three studies reported effects of NM on disability through the use of ODI [ 28 , 30 , 31 ]. The test of heterogeneity revealed the following results: χ 2 = 0.46, I 2 = 0%, P = 0.79, using a fixed effects model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported effects of NM on disability through the use of ODI [ 28 , 30 , 31 ]. The test of heterogeneity revealed the following results: χ 2 = 0.46, I 2 = 0%, P = 0.79, using a fixed effects model.…”
Section: Resultsmentioning
confidence: 99%
“…This study found that NM could effectively reduce ODI scores [ 28 , 30 , 31 ], but it doesn’t necessarily improve quality of life. In a study conducted by Plaza Manzano et al [ 32 ] on NM for lumbar spine disease, it was found that the addition of NM therapy to motor control did not result in a statistically significant change in patients’ function, as measured by the Rowland-Morris Disability Questionnaire (PMDQ), after a period of 2 months.…”
Section: Discussionmentioning
confidence: 98%
“…58,60,[63][64][65][66][67][68][69]71,73,74 In two studies, no details on the neural mobilisation were given. 62,70 For pain intensity, 10 randomised controlled trials 59,60,62,63,66,70,71,74,81,82 eight at high risk of bias 59,62,63,66,70,71,81,82 and two at low risk of bias 60,74 and two quasi-randomised trials at critical risk of bias 67,68 were included in the meta-analysis (n = 476). The results showed a large and significant effect favouring the neural mobilisation group (effect size = −1.10, 95% confidence interval: −1.96; −0.24; very low certainty of evidence).…”
Section: Low Back Painmentioning
confidence: 99%
“…Three repetitions of the MBLR approach were performed. After holding this stretch for 7-10 seconds, it was released [ 12 ]. Five treatment sessions each week were part of the two-week strategy.…”
Section: Case Presentationmentioning
confidence: 99%
“…The leg was stretched out for a considerable period (between 7 and 10 seconds), after which it was returned to the couch. For two weeks, this method was practiced five days a week, three times every session, every day [ 12 ].…”
Section: Introductionmentioning
confidence: 99%